Bipolar Disorder with Psychosis Featured in Patient with Systemic Lupus Erythematosus - Liya Maulidianti; I Putu Diatmika; Indah Sapta Wardani (Jurnal Psikiatri Surabaya, 2023)
Abstracts Introductions: Bipolar disorder (BD) is a mental disorder that imposes unusual shifts in mood, energy, activity levels, and the ability to carry out day-to-day tasks, characterized by biphasic mood episodes of mania or hypomania and depression. More than half of all individuals diagnosed with BD experience psychosis features in their lifetime. The cause of BD is not entirely known, study claims that BD may occur due to or associated with autoimmune diseases. Systemic Lupus Erythematosus (SLE) is a chronic autoimmune disease with various physical manifestations, including neuropsychiatric features. Case: This case report will discuss a 22-year-old female with BD admitted to the emergency room due to solid psychosis features. The patient was diagnosed with SLE 3 years ago but never controlled prior to the disease history. The psychiatrist’s treatment in the emergency room was an extra injection of haloperidol 5 mg IM and diazepam 10 mg IM, continued with oral medication clozapine 25 mg two times a day and additional therapies such as cognitive behavioral therapy (CBT) and family therapy. The treatment from the internist was symptomatic medication due to the acute SLE symptoms, followed by autoimmune medicines such as steroids and hydroxychloroquine. Conclusions: BD may be associated with SLE. Psychosis features generally occur in BD, usually in the manic period. Treatment should be done for both psychiatric and internal medicine problems. As the SLE symptom was controlled, the BD symptom improved.